Determination of Married Dispensation Number: 008/Pdt.p/2018/Tgm And 0012/Pdt.p/2019/Tgm in Maslahah Perspective - Tiswarni Tiswarni; Jayusman Jayusman; Aimas Soleha Rohilati (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2020)
This paper aims to analyze the judges’ considerations of the Class I B Tanggamus Religious Court in the case of the determination of the Marriage Dispensation Number 008/Pdt.P/2018/PA. Tgm and 0012/ Pdt.P/2019/PA.Tgm, and the reasons put forward by the petitioners, as well as reviewing them from the maslahahah side. This research method is descriptive qualitative, with the Ushul Fiqh approach. Collecting data through documentation and library research, using sources related to the main research problem, both primary and secondary sources with philosophical, juridical, and logical approaches, and content analysis techniques. As a result, the panel of judges gave its decision based on the fact that their marriage could be carried out immediately because the applicants were consensual and always together, and there was a concern that unwanted things would happen in religion or the law. The reasons for parents to marry off their children at a young age (under 19 years) are due to cultural factors, releasing the burden on parents, and because they are pregnant outside of marriage. From the view of maslahah, this dispensation of marriage does not bring benefit, but rather brings harm. Because the impact after marriage, it turns out that one of them always quarrels in his household so he doesn’t live together anymore. And one other even though they still live together, but their lives are very deprived and unworthy.